Overcoming esthetic challenges in the smile zone using the "roll flap procedure" - Rahul G Wagle; Chaitanya Shanbhag; Rajdeep S Pavaskar (Wolters Kluwer Medknow Publications, 2010)
Hard and soft tissue alveolar ridge deformities occur following the extraction of teeth, creating functional and esthetic tooth replacement challenges, especially in the esthetic zone. A surgical technique using a roll flap technique for ridge augmentation is discussed which when combined with conventional fixed partial dentures for tooth replacement creates a template of the labial and interproximal sulcus at the edentulous site, allowing for the molding of an ovate pontic resulting in greatly improved esthetics in an esthetically compromised case. This results in vastly improved restorative emergence profiles with minimal or no change in the height of the labial gingival margin and the form and height of the interproximal papillae with adjacent teeth. This technique enhances soft tissue contours adjacent to the definitive restoration that vary little from those of the original natural tooth.